Optimizing the role of nurses in assisting families with non-communicable diseases in the community - Sakke Tira, Deviarbi; Lorna Lolo, Lestari; Yunus, Muh; Sumiati, Sumiati; Bakri, Burhanuddin (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Non-communicable diseases (NCDs) have become a significant health problem in many communities, including in Indonesia. The role of nurses in assisting families with NCDs is crucial to improving the quality of life of patients and their families. This Community Service Program aims to optimize the role of nurses in accompanying families who have members with PTM. The methods used in this program include health training and education, home visits, and the formation of family support groups. Community nurses are provided with training on NCD management, effective communication with patients and families, and holistic mentoring strategies. Home visits are conducted to provide direct assistance and ensure the implementation of the right treatment plan. The establishment of a family support group aims to create a supportive environment for patients and families in dealing with NCDs. The results of this program show an increase in the knowledge and skills of nurses in accompanying families with NCDs. In addition, there has been an increase in patient compliance with treatment plans, as well as an improvement in the quality of life of patients and their families. This program concludes that optimizing the role of nurses in assisting families with NCDs can have a significant positive impact on NCD management in the community.